FORTIFIED FEED OF AVOCADO (Persea americana) LEAF EXTRACT FOR SEPTICEMIA MOTILE AEROMONAD DISEASE PREVENTION IN CATFISH - Ardiansyah Kurniawan; Dara Novera Jumita; eva prasetiyono (Scripta Biologica, 2019)
Disease caused by the bacterium A. hyrophila known as MAS (Motile Aeromonad Septicaemia) decreases survival and growth in Catfish. Phytopharmaca is a potential solution to replace antibiotics. One of the phytopharmaca which has the potential to be effective, inexpensive, safe for humans, and environmentally friendly is avocado (Persea americana) with active compounds such as alkaloids, flavonoids, saponins, and tannins. The potential for prevention of bacterial diseases with avocado leaf extract on the clinical symptoms of fish in MAS disease needs to be scientifically proven to be applicable to aquaculture economically and environmentally sustainable. This study uses an experimental method with several stages, namely testing LD50, in vitro and in vivo tests. The LD50 concentration of A. hydrophila is at a density of 102 cfu/ml. The filtrate of avocado leaf maceration showed that a clear zone diameter is equivalent to penicillin in the in-vitro test. Fortification of avocado leaf extract on feed is quite effective in preventing MAS disease in the in-vivo test. The fastest of MAS disease clinical symptoms recovery is at a dose of 100 ppt and 300 ppt on the 7th day. The highest Survival Rate (SR) was found at a dose of 100 pp (100%) which was equivalent to negative control and followed by a dose of 200 ppt (73.33%), 300 ppt (66.67%) and positive control (46.67%).